THE RELATIONSHIP BETWEEN MATERNAL CHARACTERISTICS AND PARENTING PATTERNS IN FEEDING WITH THE INCIDENCE OF MALNUTRITION STATUS IN TODDLERS IN UPTD PUSKESMAS GARAWANGI KUNINGAN REGENCY IN 2023 - Eli Nurindah Sari; Sinar Pertiwi; Helmi Diana (Jurnal Ilmiah Kebidanan (The Journal Of Midwifery), 2024)
Underweight and severely underweight are prevalent nutritional concerns among children under five years old. This study involved 139 mothers of malnourished toddlers and utilized a descriptive correlational approach. The findings revealed significant associations between maternal education (p-value = 0.000), maternal age (p-value = 0.000), maternal occupation (p-value = 0.001), number of children (p-value = 0.005), and parenting feeding practices (p-value = 0.018) with the incidence of nutritional deficiencies in toddlers. These results underscore the relationship between maternal characteristics, feeding practices, and the nutritional status of toddlers. It is recommended that mothers of toddlers prioritize their children's nutritional needs to ensure healthy growth and development.